Manajemen Konflik dan Motivasi Kerja Perawat Pelaksana - T. Pono, Susilarati; Tutik Agustini; Fatma Jama (Window of Nursing Journal, 2023)
Conflict is one of the most common problems in the nurse's work environment. Good conflict management for nurses is needed so that conflicts that occur have a positive impact so that they can increase nurses' work motivation. The purpose of the study was to determine the relationship between conflict management and work motivation of implementing nurses at the Tobelo Regional General Hospital, North Maluku Province. The type of research used is quantitative with correlational research methods with cross sectional study design. Determination of the sample in this study using purposive sampling with a sample size of 66 people calculated using the Slovin formula. Data collection tool in the form of a questionnaire. Data analysis used correlative statistical test. The results of the study generally found that there was a relationship between conflict management and work motivation. (Sig. (2-tailed) = 0.001). While specifically the results obtained are compromise (Sig. (2-tailed) = 0.041), competition (Sig. (2-tailed) = 0.032), accommodation (Sig. (2-tailed) = 0.895), softening (Sig. (2-tailed) -tailed) = 0.001), avoiding (Sig. (2-tailed )= 0.652) and collaboration (Sig. (2-tailed = 0.009). The results of data processing were obtained from 53 nurses (80.3%) who had good conflict management, 30 nurses (45.5%) felt well motivated with their work.While of 13 nurses (19.7%) whose conflict management was not good, 36 nurses (54.5%) felt less motivated with their work. Conclusions and Suggestions that conflict management have a significant impact on nurses' work motivation.Hospital management is expected to facilitate nurses to get education and training about conflict and conflict management so as to improvye the ability of nurses in choosing appropriate conflict management strategies.